Human Ethics and Virtues: Rethinking the Homo-Economicus Model - Sanjit Dhami (Center for Economic Studies and ifo Institute (CESifo), 2017)
The neoclassical model in economics envisages humans as amoral and self-regarding (Econs). This model, also known as the homo-economicus model, is not consistent with the empirical evidence. In light of the evidence, the continued use of the homo-economicus model is baffling. It also stymies progress in the field by putting the burden of adjustment on auxiliary assumptions that need to compensate for an unrealistic picture of human motivation and behavior. This essay briefly outlines the evidence for a more inclusive picture of humans in which ethics and morality play a central role. It argues for replacing the homo-economicus model with a homo-behavioralis model that has already enabled great progress to be made in the field of behavioral economics.
Keywords: D90; D64; 330; ethics; morality; intrinsic motivation; consequentialistic choices; lying-aversion; guilt-aversion; markets and morality; moral balancing; self-image; self-serving justifications; partial lying; third party punishment; delegation; social identity; moral suasion